To turn the tide - Stirling, S. M. (Stirling, S. M. To make the darkness light, 2024)
"It's the end of the world as we know it. Everyone could see it coming. But one man could do something about it. Oh, he couldn't avert the nuclear holocaust, but a scientist in Austria, ruthlessly using billions of research dollars for his own purposes, set himself up an out: he created a time machine, and filled a warehouse with low-tech survival gear. Too bad he didn't get to use it himself. Instead, a team of American grad students, led by their professor, is sent back to the late Roman Empire. Even though they are experts in this time and place, they are about to realize that books and actual experience are very different things. If they can survive, they hope to remake the world into a better place. But that's a big "if.""--